First report on the enzymatic and immune response of Metarhizium majus bag formulated conidia against Spodoptera frugiperda: An ecofriendly microbial insecticide - Perumal, Vivekanandhan; Kannan, Swathy; Alford, Lucy; Pittarate, Sarayut; Geedi, Ruchika; Elangovan, Dilipan; Marimuthu, Ramachandran; Krutmuang, Patcharin (Frontiers in Microbiology, 2023)
Entomopathogenic fungi from microbial sources are a powerful tool for combating insecticide resistance in insect pests. The purpose of the current study was to isolate, identify, and evaluate bag-formulated entomopathogenic fungal conidial virulence against insect pests. We further investigated the enzymatic responses induced by the entomopathogenic fungi as well at the effect on a non-target species. Entomopathogenic fungi were isolated from the Palamalai Hills, India, using insect baith method, and the Metarhizium majus (MK418990.1) entomopathogen was identified using biotechnological techniques (genomic DNA isolation and 18S rDNA amplification). Bag-formulated fungal conidial efficacy (2.5× 103, 2.5 × 104, 2.5 × 105, 2.5 × 106, and 2.5 × 107 conidia/mL) was evaluated against third instar larvae of Spodoptera frugiperda at 3, 6, 9, and 12 days of treatment, and acid and alkaline phosphatases, catalase, and superoxide dismutase enzymatic responses were evaluated at three days post-treatment. After 12 days of treatment, non-target assays on the earthworm Eudrilus eugeniae were performed using an artificial soil assay. Results of the bag formulated fungal conidial treatment showed that S. frugiperda had high susceptibility rates at higher concentrations (2.5 × 107 conidia/mL) of M. majus. Lower concentration of 2.5×103 conidia/mL caused 68.6% mortality, while 2.5×107 conidia/mL caused 100 % mortality at 9 days post treatment. Investigation into enzymatic responses revealed that at 3 days post M. majus conidia exposure (2.5×103 conidia/mL), insect enzyme levels had significantly changed, with acid and alkaline phosphatases, and catalase enzymes significantly reduced and superoxide dismutase enzymes significantly raised relative to the control. After 12 days of treatment, no sublethal effects of M. majus conidia were observed on E. eugeniae, with no observed damage to gut tissues including lumen and epithelial cells, the nucleus, setae, coelom, mitochondria, and muscles. This study offers support for the use of fungal conidia in the target-specific control of insect pests.